Evaluation of the European Policies in Support of Ultraperipheric Regions, Azores, Madeira, Canarias, Guadalupe, Martinique, Guyane and Reunion - Tomaz Ponce Dentinho; Mário Amaral Fortuna; Rui Gonçalves Luís; José Cabral Vieira (European Regional Science Association (ERSA), 2001)
The paper looks at the development of the EU's outermost regions. We develop a model not only to explain the effects caused by peripherality but also to evaluate the European policies towards ultra peripheral regions. Ultra-peripherality is an economic and social phenomenon associated to a geographical structure characterised by two attributes: size and access. The structure of the model to analyse size, or supply performance, can be represented in three interrelated blocks: i) the first block explains the effect on the population of driving activities in island economies: exports, external aid for employment and external subsidies; ii) the second block establishes the relationships between population and activities associated to the provision of goods and services not receiving external aid; iii) the third block estimates the product and the income of the region by multiplying the quantity of each type of activity, measured in terms of the number of jobs involved. The structure of the model for access, or demand performance, is in a way implicit in the model of size through the population indicator; however, the population indicator does not clearly translate variations of accessibility to the region being. The present study uses the demographic potential to arrive at an accessibility indicator that uses easily accessible statistical data: the population and the traffic of passengers. We conclude that the impact of ultra-peripheral policies are weaker in the regions more dependent on external public transferences, the connection with neighbour countries can produce important effects in the economy, the elimination of the "sea rights" in most of the regions could generate important impacts in the respective development process, the effective liberalisation of air transportation will lead to a strong increase in the accessibility and the development process based on import substitution and external public transferences can led to a big increase in the population and created a great dependence on the "sea rights".
Keywords: 330